Improvement of Left Ventricular Function under Cardiac Resynchronization Therapy Goes along with a Reduced Incidence of Ventricular Arrhythmia - Eickholt, Christian; Siekiera, Marcus; Kirmanoglou, Kiriakos; Rodenbeck, Astrid; Heussen, Nicole; Schauerte, Patrick; Lichtenberg, Artur; Balzer, Jan; Rassaf, Tienush; Perings, Stefan; Kelm, Malte; Shin, Dong-In; et al. (PLOS ONE, 2012)
Objectives The beneficial effects of cardiac resynchronization therapy (CRT) are thought to result from favorable left ventricular (LV) reverse remodeling, however CRT is only successful in about 70% of patients. Whether response to CRT is associated with a decrease in ventricular arrhythmias (VA) is still discussed controversially. Therefore, we investigated the incidence of VA in CRT responders in comparison with non-responders. Methods In this nonrandomized, two-center, observational study patients with moderate-to-severe heart failure, LV ejection fraction (LVEF) ≤35%, and QRS duration >120 ms undergoing CRT were included. After 6 months patients were classified as CRT responders or non-responders. Incidence of VA was compared between both groups by Kaplan-Meier analysis and Cox regression analysis. ROC analysis was performed to determine the aptitude of LVEF cut-off values to predict VA. Results In total 126 consecutive patients (64±11years; 67%male) were included, 74 were classified as responders and 52 as non-responders. While the mean LVEF at baseline was comparable in both groups (25±7% vs. 24±8%; P = 0.4583) only the responder group showed an improvement of LVEF (36±6% vs. 24±7; p<0.0001) under CRT. In total in 56 patients VA were observed during a mean follow-up of 28±14 months, with CRT responders experiencing fewer VA than non-responders (35% vs. 58%, p<0.0061). Secondary preventive CRT implantation was associated with a higher likelihood of VA. As determined by ROC analysis an increase of LVEF by >7% was found to be a predictor of a significantly lower incidence of VA (AUC = 0.606). Conclusions Improvement of left ventricular function under cardiac resynchronization therapy goes along with a reduced incidence of ventricular arrhythmia.